Cellulose Fundamental Aspects - van de Ven, Theo; Godbout, Louis (IntechOpen, 2013)
Cellulose is destined to play a major role in the emerging bioeconomy. Awareness of the environment and a depletion of fossil fuels are some of the driving forces for looking at forest biomaterials for an alternative source of energy, chemicals and materials. The importance of cellulose is widely recognized world-wide and as such the field of cellulose science is expanding exponentially. Cellulose, the most abundant biopolymer on earth, has unique properties which makes it an ideal starting point for transforming it into useful materials. To achieve this, a solid knowledge of cellulose is essential. As such this book on cellulose, the first in a series of three, is very timely. It deals with fundamental aspect of cellulose, giving the reader a good appreciation of the richness of cellulose properties. Book Cellulose - Fundamental Aspects is a good introduction to books Cellulose - Medical, Pharmaceutical and Electronic Applications and Cellulose - Biomass Conversion , in which applications of cellulose and its conversion to other materials are treated.